Decitabine With or Without Micro-Transplantation for the Treatment of Intermediate or High-Risk Myelodysplastic Syndrome: A Chinese Single-Center Retrospective Study of 22 Patients - Li, MinMing; Li, Chao; Geng, SuXia; Chen, XiaoMei; Wu, Ping; Deng, ChengXin; Chen, XiaoFang; Lu, ZeSheng; Weng, JianYu; Du, Xin (Frontiers in Oncology, 2021)
The treatment outcomes of intermediate or high-risk myelodysplastic syndrome (MDS) remain unsatisfactory. This study was designed to evaluate the safety and efficacy of human leukocyte antigen (HLA)-mismatched hematopoietic stem cell micro-transplantation (MST) in patients with MDS. A total of 22 patients with MDS, ranging between the ages of 39 to 74, were enrolled in this study. Eleven patients were given decitabine, a DNA methyltransferase inhibitor, combined with HLA-mismatched MST (MST-DAC group), and the remaining patients were given decitabine only (DAC group). The median overall survival (OS) of the MST-DAC group was higher than that of the DAC group (24 months vs. 14.3 months; HR 0.34; 95% CI: 0.11-1.96; P = 0.04), although it is a study with small samples. The overall response rate (ORR), marrow complete remission (mCR), plus hematological improvement (HI) rates of the MST-DAC group were higher than that of the DAC group (81.8% vs. 54.5%, P = 0.36; 63.6％ vs. 18.2％, P = 0.09, respectively); however, there were no statistical differences between the two groups, which may be attributed to the limited number of cases evaluated in this study. No graft-versus-host disease was observed in the MST-DAC group. Patients in the MST-DAC group demonstrated a slightly lower incidence of hematological and non-hematological adverse events (AEs). Decitabine combined with HLA-mismatched MST may provide a novel, effective, and safe treatment for use in intermediate or high-risk MDS pathologies.